Culturally Adapted Cognitive Behavioral Therapy for Moderate Depression and Non-Suicidal Self-Injury Patients - Kumar, Anand; Hyder Shaikh, Irsa; Sher, Zainab; A Malik, Mareen (Indus Journal of Bioscience Research, 2024)
Objective: This study aimed to evaluate the effectiveness of culturally adapted cognitive behavioral therapy (CA-CBT) for treating moderate depression and NSSI in Pakistani patients. Methods:  A randomized controlled trial was conducted with 100 participants aged 18-35 years, diagnosed with moderate depression and engaging in NSSI behaviors. Participants were randomly assigned to either the CA-CBT intervention group (n=50) or the standard care control group (n=50). The CA-CBT program integrated Islamic teachings and cultural practices with conventional CBT techniques. Depression and NSSI behaviors were assessed at baseline, post-treatment, and a 3-month follow-up using the Beck Depression Inventory (BDI) and the Self-Injury Behavior Scale (SIBS). Results: The CA-CBT group showed significant reductions in depressive symptoms (p